Independent work as a condition for teacher's self-improvement in the educational process of additional vocational education institutions - José Fernando Toaquiza Chancusig; Olga Samanda Abedrabbo Ramos (Dominio de las Ciencias, 2024)
In this article, the established role for the importance of self-management and ongoing self-improvement of teachers within the teacher training system will be revealed. It conceptually defines independent work as the study, research and critical analysis activities of practice that teachers carry out autonomously. The key principles of andragogy that should guide autonomous work will be described, such as: starting from the learning needs of the participant, allowing self-management of content and methods, considering motivation and previous experience. It is also based on criteria such as systematicness, practical utility, self-regulation and self-assessment. Subsequently, an organized 7-step algorithm is explained to effectively structure teachers' independent work. Likewise, it proposes tools to develop teachers' ability for self-reflection and metacognition, such as self-control cards. It also raises the importance of linking content to the solution of real pedagogical problems that teachers face.